Nomogram Predicting the Benefits of Adding Concurrent Chemotherapy to Intensity-Modulated Radiotherapy After Induction Chemotherapy in Stages II–IVb Nasopharyngeal Carcinoma - Sai-Lan Liu; Sai-Lan Liu; Xue-Song Sun; Xue-Song Sun; Zi-Jian Lu; Zi-Jian Lu; Qiu-Yan Chen; Qiu-Yan Chen; Huan-Xin Lin; Huan-Xin Lin; Lin-Quan Tang; Lin-Quan Tang; et al. (Frontiers in Oncology, 2020)
BackgroundTo compare the efficacy of induction chemotherapy plus concurrent chemoradiotherapy (IC+CCRT) versus induction chemotherapy plus radiotherapy (IC+RT) in patients with locoregionally advanced nasopharyngeal carcinoma (NPC).Patients and MethodsOne thousand three hundred twenty four patients with newly-diagnosed NPC treated with IC+CCRT or IC+RT were enrolled. Progression-free survival (PFS), distant metastasis-free survival (DMFS), overall survival (OS), locoregional relapse-free survival (LRFS), and acute toxicities during radiotherapy were compared using propensity score matching (PSM). A nomogram was developed to predict the 3- and 5-year PFS with or without concurrent chemotherapy (CC).ResultsPSM assigned 387 patients to the IC+CCRT group and IC+RT group, respectively. After 3 years, no significant difference in PFS (84.7 vs. 87.5%, P = 0.080), OS (95.5 vs. 97.6%, P = 0.123), DMFS (89.7 vs. 92.8%, P = 0.134), or LRFS (94.0 vs. 94.1%, P = 0.557) was noted between the groups. Subgroup analysis indicated comparable survival outcomes in low-risk NPC patients (II–III with EBV DNA <4,000 copies/ml) between the groups, although IC+RT alone was associated with fewer acute toxicities. However, IC+CCRT was associated with significantly higher 3−year PFS, OS, DMFS, and LRFS rates, relative to IC+RT alone, in high-risk NPC patients (IVa-b or EBV DNA ≥4,000 copies/ml). Multivariate analysis showed that T category, N category, EBV DNA level, and treatment group were predictive of PFS, and were hence incorporated into the nomogram. The nomogram predicted that the magnitude of benefit from CC could vary significantly.ConclusionsIC+RT had similar efficacy as IC+CCRT in low-risk NPC patients, but was associated with fewer acute toxicities. However, in high-risk patients, IC+CCRT was superior to IC+RT.